Treatment of Polarized Cystic Fibrosis Airway Cells With HGF Prevents VX-661-Rescued F508del-CFTR Destabilization Caused by Prolonged Co-exposure to VX-770 - Matos, Ana M. (2022)
Cystic fibrosis (CF), the most common inherited disease in Caucasians, is caused by mutations in CFTR, the most frequent of which is F508del. F508del causes ER retention and degradation of the mutant CFTR protein, but also defective channel gating and decreased half-life at the plasma membrane. Despite the recent successes with small molecule CFTR modulator drugs, the folding-corrector/gating-potentiator drug combinations approved for CF individuals carrying F508del-CFTR have sometimes produced severe side effects. Previously, we showed that a prolonged, 15-days treatment of polarized bronchial epithelial monolayers with the VX-809+VX-770 combination resulted in epithelial dedifferentiation effects that we found were caused specifically by VX-809. Moreover, prolonged VX-770 exposure also led to the destabilization of VX-809-rescued F508del-CFTR. Notably, co-treatment with the physiological factor HGF prevented VX-809-mediated epithelial differentiation and reverted the destabilizing effect of VX-770 on VX-809-rescued CFTR. Here, we show that prolonged treatment with VX-661, a second-generation corrector developed based on VX-809 structure, does not perturb epithelial integrity of polarized bronchial epithelial monolayers. Yet, its efficacy is still affected by co-exposure to VX-770, the potentiator present in all VX-661-containing combination therapies approved in the United States and Europe for treatment of F508del-CFTR carriers. Importantly, we found that co-treatment with HGF still ameliorated the impact of VX-770 in F508del-CFTR functional rescue by VX-661, without increasing cell proliferation (Ki-67) or altering the overall expression of epithelial markers (ZO-1, E-cadherin, CK8, CK18). Our findings highlight the importance of evaluating the cellular effects of prolonged exposure to CFTR modulators and suggest that the benefits of adding HGF to current combination therapies should be further investigated.